2006
DOI: 10.1590/s1677-55382006000100005
|View full text |Cite
|
Sign up to set email alerts
|

Urinary retention and the role of indwelling catheterization following total knee arthroplasty

Abstract: Introduction:We aimed to investigate the rate of urinary retention after knee arthroplasty, the various factors involved in predicting those at risk for retention and to assess the impact of retention and catheterization on joint sepsis. Materials and Methods: A retrospective review was conducted of all available case notes of patients undergoing total knee arthroplasty in a consecutive 2-year period (2000)(2001)(2002). Adequate data was available for 142 patients. Results: 142 patients underwent total knee ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 12 publications
0
15
3
Order By: Relevance
“…Several other factors have been indicated for giving an increased incidence of POUR such as increased prostate specific antigen, previous history of POUR 17 and a peak urinary flow of <17ml/s 18 . Other factors or situations tend to necessitate catheterisation, eg extensive revision surgery and bilateral joint replacements.…”
Section: Discussionmentioning
confidence: 99%
“…Several other factors have been indicated for giving an increased incidence of POUR such as increased prostate specific antigen, previous history of POUR 17 and a peak urinary flow of <17ml/s 18 . Other factors or situations tend to necessitate catheterisation, eg extensive revision surgery and bilateral joint replacements.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that gender is not correlated significantly with the development of POUR [5,10,11]. Also, Tammela et al [14] suggested that there was no significant difference in frequencies of persistent micturition difficulty after the first catheterization for POUR between male and female patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 Retention is commonly treated with urethral catheterisation, which can itself induce bacteraemia and further increase the risk of deep joint sepsis. [1][2][3] Previous studies report an incidence of deep sepsis following primary total hip replacement (THR) of <2% 4 rising to as much as 6.2% 1,5 with postoperative urethral catheterisation.…”
mentioning
confidence: 99%
“…As a consequence, a number of studies have tried to better define the risk factors for retention by addressing the surgical factors 5,[8][9][10][11] and individual patient factors 5,8,10,12 associated with retention. To date, there is compelling evidence that male sex, increasing age and epidural opioids pose independent risk factors for the development of retention.…”
mentioning
confidence: 99%